2023
DOI: 10.3390/healthcare11142016
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion during COVID-19 in Non-WEIRD Countries: A Narrative Review

Abstract: The coronavirus disease 2019 (COVID-19) pandemic impacted people’s mental health negatively worldwide, including in non-WEIRD (Western, Educated, Industrialised, Rich and Democratic) countries. Self-compassion, kindness and understanding towards oneself in difficult times have received increasing attention in the field of mental health. Self-compassion is strongly associated with good mental health in various populations. This narrative review aimed to synthesise the evidence on self-compassion and mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…One of the main goals of this study was to examine the association between compassionate self-responding and indicators related to mental health. In line with previous findings (e.g., [76,77]), we demonstrated that trajectory groups reflecting higher levels of compassionate self-responding were associated with greater life satisfaction, more happiness, better sleep quality, higher sleep quantity (marginal), and lower levels of negative emotions, as compared to trajectory groups reflecting lower levels of compassionate self-responding. This study replicates well-established findings in the literature suggesting that self-compassion is positively associated with mental health (e.g., [78,79]).…”
Section: The Role Of Self-compassion In Mental Healthsupporting
confidence: 91%
“…One of the main goals of this study was to examine the association between compassionate self-responding and indicators related to mental health. In line with previous findings (e.g., [76,77]), we demonstrated that trajectory groups reflecting higher levels of compassionate self-responding were associated with greater life satisfaction, more happiness, better sleep quality, higher sleep quantity (marginal), and lower levels of negative emotions, as compared to trajectory groups reflecting lower levels of compassionate self-responding. This study replicates well-established findings in the literature suggesting that self-compassion is positively associated with mental health (e.g., [78,79]).…”
Section: The Role Of Self-compassion In Mental Healthsupporting
confidence: 91%
“…Moreover, self-report measures are susceptible to response biases [53]. The study consisted of predominantly white British females; therefore, more investigation is needed into the experiences of non-white samples, other genders, and those from developing countries and different cultures [54,55]. The use of opportunity sampling may have limited the generalisability of the findings in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The included papers were reviewed by three co-authors (HA, AK, MA, and OT) who were specialists in mental health and migrants. The findings were thematically synthesised by YK [44]. The synthesised findings were reviewed by all co-authors for coherency and clarity.…”
Section: Methodsmentioning
confidence: 99%